High temperature resistant silicone resin and preparation method thereof

CN122898145APending Publication Date: 2026-10-13HUBEI UNIV OF EDUCATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611100891.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本申请提供了一种耐热老化的硅树脂及其制备方法和应用,旨在改善现有氟硅树脂在长期高温氧化环境下易发生主链降解、界面键断裂导致性能衰减的问题,提高材料的耐高温性能和高温处理后的力学性能保持率

Benefits of technology

本申请通过在氟硅树脂体系中协同引入含三嗪环硅烷偶联剂与含环氧基硅烷偶联剂,在固化过程中原位构建刚柔并济的三嗪环-环氧桥联协同增强网络。该网络结构可提升填料与树脂基体的界面结合强度,增强交联网络的热化学稳定性,有效减少高温氧化环境下界面键断裂和聚合物主链降解;同时,三嗪环的刚性骨架与环氧开环形成的柔性醚键链段协同作用,既能抑制高温链段运动,又能分散热应力,减缓材料脆化进程,从而使所得氟硅树脂在长期高温老化后仍能保持良好的力学性能。本申请实现了氟硅树脂耐热老化性能与高温力学性能保持率的提升,具有广泛的工程应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a high-temperature-resistant silicone resin and a preparation method thereof. The high-temperature-resistant silicone resin comprises the following raw materials in parts by mass: 100 parts by mass of hydroxyl-terminated fluorosilicone raw rubber, 0.5-2 parts by mass of triazine ring-containing silane coupling agent, 0.05-1 parts by mass of dibutyltin dilaurate, 10-50 parts by mass of reinforcing filler, and 0.5-5 parts by mass of crosslinking agent. The triazine ring-containing silane coupling agent is obtained by nucleophilic substitution reaction between part of chlorine atoms in cyanuric chloride and amino silane coupling agent, and the molar ratio of cyanuric chloride to amino silane coupling agent is 1: (2-3). By introducing the triazine ring-containing silane coupling agent and epoxy group-containing silane coupling agent into the fluorosilicone resin system, a rigid-flexible combined triazine ring-epoxy bridging synergistic reinforcing network is constructed during the curing process, the interfacial bonding strength between the filler and the resin matrix is improved, the thermal chemical stability of the crosslinking network is enhanced, the interfacial bond rupture and polymer main chain degradation under high-temperature oxidation environment are reduced, and the high-temperature resistance of the silicone resin is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of silicone rubber technology, specifically to high-temperature resistant silicone resin and its preparation method. Background Technology

[0002] Fluorosilicone resins, a class of polysiloxane materials with fluorinated groups such as trifluoropropyl groups introduced into the side groups of the main chain, successfully combine the wide temperature range stability of organosilicon with the excellent oil and solvent resistance of fluorochemistry, making them irreplaceable in aerospace sealing, high-end automotive engine compartment components, and protective coatings in harsh chemical environments. However, when these materials are exposed to high-temperature oxidizing environments for a long time, their molecular structure faces a dual challenge: on the one hand, the siloxane main chain (Si-O-Si) may undergo thermo-oxidative chain breakage, leading to a decrease in molecular weight and a decline in mechanical properties; on the other hand, although the fluorinated side groups (-CF3) themselves have high bond energies, their strong electron-withdrawing effect may exacerbate the instability of adjacent silicon atoms under thermal stress, while the interfacial bonding between the filler and the resin matrix is ​​also prone to becoming a weak point in thermo-oxidative aging. This microscopic structural degradation directly manifests macroscopically as powdering, cracking, loss of adhesion, and sealing failure in coatings or molded products after long-term thermal aging, severely restricting the application of fluorosilicone resins in scenarios with higher reliability requirements.

[0003] In existing technologies, the main approaches to improving the heat aging resistance of silicone resins include: introducing high heat-resistant fillers to enhance thermomechanical strength and thermal barrier effect; using silane coupling agents to surface-treat fillers to enhance their interfacial compatibility and bonding force with the resin matrix; or introducing more thermally stable structural units, such as bulky aryl groups, into the molecular chain. For example, existing technologies often use epoxy-containing silane coupling agents (such as KH-560) to treat fillers or as modifiers. Their epoxy groups can participate in the reaction during curing, forming ether bonds, which helps to improve interfacial bonding force and introduce flexibility, alleviating internal stress. However, this type of single flexible modification strategy has limited effect on improving the intrinsic thermal stability of silicone resins and is difficult to fundamentally inhibit the thermo-oxidative degradation of the main chain under long-term high temperatures.

[0004] On the other hand, triazine rings, as nitrogen-containing aromatic rings with high resonance stability and bond energy, have been widely recognized in the field of polymer materials for their excellent heat resistance and char-forming properties. However, research on introducing them into silicone resin systems through silane coupling agents and co-designing them with specific flexible units is still lacking.

[0005] Existing technical solutions have obvious limitations: First, a single type of silane coupling agent cannot simultaneously achieve high thermal stability and excellent crack resistance in the rigid three-dimensional network of silicone resin; second, if the physical reinforcement of the filler lacks stable and tough interfacial chemical bonding, it is prone to becoming a stress concentration point and failure origin under long-term thermal cycling; in addition, small molecule antioxidants or heat-resistant additives also face the dilemma of easy migration and volatilization under the high-temperature processing and use conditions of silicone resin, resulting in insufficient durability.

[0006] Therefore, how to simultaneously improve the heat aging resistance and mechanical durability of silicone resin has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0007] This application provides a heat-resistant silicone resin, its preparation method, and its application, aiming to improve the problem that existing fluorosilicone resins are prone to main chain degradation and interfacial bond breakage under long-term high-temperature oxidative environment, resulting in performance degradation, and to improve the high-temperature resistance and mechanical property retention rate of the material after high-temperature treatment.

[0008] In a first aspect, this application provides a high-temperature resistant silicone resin comprising the following raw materials in parts by weight: 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 0.5 to 2 parts by weight of triazine cyclosilane coupling agent, 0.05 to 1 part by weight of dibutyltin dilaurate, 10 to 50 parts by weight of reinforcing filler, and 0.5 to 5 parts by weight of crosslinking agent; The triazine cyclosilane coupling agent is obtained by a nucleophilic substitution reaction between some chlorine atoms in cyanuric chloride and an aminosilane coupling agent, and the molar ratio of cyanuric chloride to aminosilane coupling agent is 1:(2-3).

[0009] According to this application, by introducing a triazine cyclosilane coupling agent into the fluorosilicone resin system, the crosslinking density, thermomechanical strength and thermal stability of the material can be improved, thereby enhancing the long-term durability of the fluorosilicone resin under high-temperature conditions.

[0010] Specifically, in the fluorosilicone resin system, this application introduces a triazine-containing silane coupling agent as the main heat-resistant reinforcing unit. This coupling agent can form a strong Si-O-Si chemical anchor with the filler and resin matrix through the silane end groups. The triazine ring at its molecular core, as a nitrogen-containing aromatic ring, has higher resonance stability and bond energy compared to the benzene ring. As a large, rigid skeletal unit in the cured network, it helps to suppress the high-temperature movement of polymer chain segments, thereby improving the material's thermal stability. Furthermore, the nitrogen atom in the triazine ring has lone pairs of electrons and strong electronegativity; its electronic effect can influence the electronic environment of adjacent chemical bonds in a localized space, thus providing a certain degree of thermal stabilization to the main chain and side chains. Simultaneously, if the triazine ring is located near the fluorine-containing side chain, the local polarity or inductive effect may further improve the electronic environment of the surrounding groups, thereby contributing to improved local thermal stability.

[0011] In cyanuric chloride, the chlorine atom undergoes a nucleophilic substitution reaction with the amino group of the aminosilane, forming a CN bond. This allows the resulting product to construct a rigid triazine ring center and alkoxysilane functional end groups on the same molecular backbone. The high resonance stability of the triazine ring and the high bond energy of C=N / CN impart excellent thermal stability, which helps reduce chain segment movement and thermal degradation reactions at high temperatures. The symmetrical planar structure of the triazine ring can disperse thermal stress and provide a stereochemical shielding effect. The terminal alkoxysilane functional groups can condense with the hydroxyl groups on the filler surface or the resin matrix during subsequent curing, achieving interfacial anchoring. The resulting triazine ring-containing silane coupling agent maintains both high thermal stability and good interfacial reactivity, which helps to construct stable rigid crosslinking nodes in fluorosilicone resin systems, improving the thermomechanical properties and long-term thermal aging resistance of the material.

[0012] The initial structure of the three chlorine atoms in the cyanuric chloride molecule is symmetrical. During nucleophilic substitution, the reactivity of the remaining chlorine atom decreases nonlinearly due to electronic and steric effects with each substitution, forming a reactivity gradient. By controlling the molar ratio of aminosilanes (1:2-3), the reaction can be made to primarily connect two silane segments to the triazine ring. This can tighten the chemical bonds of the triazine ring electronically through a continuous inductive effect, thereby raising its intrinsic thermal decomposition energy barrier. Simultaneously, this structure possesses both anchoring and bridging capabilities and moderate structural rigidity, potentially reducing the dilution of the rigid center by the third flexible long chain and the possible local embrittlement of the network. The bissilane functional group enables its efficient anchoring as a stable bridging point in fluorosilicone resins. This allows the coupling agent to achieve a balance between maintaining core rigidity, providing electronic stability, and achieving effective crosslinking, helping to inherently construct a self-resistant, firmly connected, and durable crosslinked network, thereby improving the material's performance retention at long-term high temperatures.

[0013] In addition, the reinforcing filler in the system forms a strong interfacial bond with the fluorosilicone resin matrix under the action of the silane coupling agent, which effectively transfers stress and restricts chain segment movement; the crosslinking agent initiates the crosslinking reaction between the fluorosilicone resin backbone under heating conditions to form a three-dimensional network skeleton.

[0014] Through the synergistic reaction of the above-mentioned multi-components, a highly stable cross-linked network with rigid triazine ring points and flexible ether bonds is formed in the fluorosilicone resin system, which improves the heat resistance and high-temperature mechanical property retention rate of the resin system, enabling the obtained high-temperature resistant silicone resin to maintain excellent mechanical properties and structural integrity under long-term thermal aging conditions.

[0015] In some embodiments, the raw materials further include 0.5 to 2 parts by weight of an epoxy-containing silane coupling agent and 0.01 to 0.05 parts by weight of an epoxy ring-opening catalyst, wherein the epoxy-containing silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0016] In some of the aforementioned embodiments, the introduction of a rigid structure alone may lead to a decrease in the flexibility of the crosslinked network, causing problems such as internal stress concentration, material embrittlement, and deterioration of impact resistance at high temperatures, which is detrimental to long-term application in harsh environments such as thermal cycling. To resolve this contradiction, this application introduces an epoxy-containing silane coupling agent. During the curing process, the epoxy groups open to form flexible ether chain segments. These flexible segments with internal rotational freedom can effectively absorb and disperse the internal stress generated by the rigid nodes of the triazine ring, thereby reducing the risk of brittle fracture of the material. At the same time, the ring-opening reaction of the epoxy groups can form new covalent crosslinking links with active groups such as silanol groups in the fluorosilicone resin. This additional crosslinking further constructs stable flexible connecting bridges between the rigid triazine rings, making the thermomechanical properties of the crosslinked network more balanced. The inventors have found that when γ-(2,3-epoxypropoxy)propyltrimethoxysilane is used as an epoxy-containing silane coupling agent, the resulting silicone resin has better high-temperature resistance. The reason for this may be that the trimethoxysilane terminal group has higher hydrolytic activity and crosslinking density, improving the strong interfacial anchorage with the filler and resin matrix; at the same time, the terminal epoxypropoxy structure provides high reactivity and ring-opening efficiency of the epoxy group, enabling it to efficiently construct flexible ether bond bridges. This structure achieves an optimal balance between reaction efficiency, interfacial strength, and toughening effect in the coupling agent. Epoxy ring-opening catalysts can promote epoxy ring-opening, improving the reaction efficiency between epoxy groups and active groups such as silanol groups.

[0017] In some embodiments, the triazine-containing cyclosilane coupling agent is prepared by the following steps: S1: Disperse cyanuric chloride, the first aminosilane coupling agent and the first acid scavenger in tetrahydrofuran, so that the amino group in the first aminosilane coupling agent undergoes a nucleophilic substitution reaction with some chlorine atoms in cyanuric chloride to obtain a partially substituted intermediate solution. S2: Add a second acid scavenger and a second aminosilane coupling agent to the partially substituted intermediate solution, so that the amino group in the second aminosilane coupling agent undergoes a nucleophilic substitution reaction with the remaining chlorine atoms in the partially substituted intermediate to obtain a triazine cyclosilane coupling agent.

[0018] In some of the above embodiments, the carbon atom on the triazine ring, connected to a chlorine atom, exhibits positive charge due to the strong electron-withdrawing inductive effect of the adjacent nitrogen atom, making it susceptible to nucleophilic attack from the nitrogen atom in the aminosilane. In step S1, the most reactive chlorine atom in cyanuric chloride is selectively substituted, generating a partially substituted intermediate. Simultaneously, the released hydrogen chloride is neutralized by the first acid scavenger to drive the reaction equilibrium. In step S2, the remaining highly reactive chlorine atom is activated to react with the second aminosilane coupling agent. When two chlorine atoms on the triazine ring are substituted, the introduced substituent can further stabilize the triazine aromatic ring structure through a conjugation effect and form a certain steric barrier to the remaining chlorine sites, resulting in a decrease in the nucleophilic substitution reactivity of the third chlorine atom. At the same time, the bissilane functionality allows the coupling agent to act as a highly efficient bridging unit, constructing stable rigid crosslinking points in the fluorosilicone resin curing network. Therefore, this preparation method can achieve both interfacial reactivity and crosslinking ability while retaining and enhancing its structural rigidity as a thermally stable core, laying the foundation for subsequent high-performance crosslinking networks.

[0019] In some implementations, in step S1: The molar ratio of the cyanuric chloride, the first aminosilane coupling agent, and the first acid scavenger is 1:(1.0-1.5):(1.0-2).

[0020] In some of the above embodiments, the degree of nucleophilic substitution reaction is regulated by controlling the molar ratio of the first aminosilane coupling agent to cyanuric chloride within the range of (1.0–1.5):1. This ratio allows the highly reactive chlorine atom to be fully substituted, thereby obtaining a partially substituted intermediate. This enables the triazine ring skeleton to be connected to the first silane segment via a CN bond, constructing a core rigid structure for the final product. Furthermore, it preserves reaction sites for the substitution reaction of the second aminosilane in subsequent steps, allowing the introduction of an alkoxysilane structure at the other end of the molecule, thus achieving the combination of the rigid center of the triazine ring and the silane functional group.

[0021] In some implementations, in step S2: The molar ratio of the second aminosilane coupling agent, the second acid scavenger, and cyanuric chloride in step S1 is (1.0-1.5):(1.0-2):1.

[0022] In some of the above embodiments, by controlling the molar ratio of the second aminosilane coupling agent to cyanuric chloride within the range of (1.0–1.5):1, the amino group can react with the remaining C-Cl bonds in the cyanuric chloride. Under this ratio, the triazine ring skeleton can maintain good structural integrity. When two chlorine atoms on a triazine ring are substituted, the remaining chlorine atoms have low reactivity. Therefore, the side chains of the triazine ring tend to be grafted with two alkoxysilane structures, giving the resulting triazine-containing bissilane coupling agent both excellent thermal stability and interfacial reactivity. This ratio design not only facilitates the reaction transformation of the remaining C-Cl bonds but also avoids the self-condensation side reaction that may be caused by excessive aminosilane, thus ensuring the acquisition of structurally regular bissilane functionalized products.

[0023] In some embodiments, the first aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0024] In some of the above embodiments, both γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane have alkoxysilane and terminal primary amino structures: the primary amino group at one end has high nucleophilic activity and can undergo efficient selective nucleophilic substitution reaction with chlorine atoms in cyanuric chloride, ensuring the successful construction of the triazine ring structure; the alkoxysilane at the other end end end endows the product with excellent hydrolytic condensation ability, enabling it to form a strong Si-O-Si interface chemical anchor with the filler and resin matrix in the final fluorosilicone resin curing system.

[0025] In some embodiments, the second aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane. As an example, in one embodiment of the present invention, both the first and second aminosilane coupling agents are γ-aminopropyltrimethoxysilane.

[0026] In some embodiments, the first acid scavenger includes at least one of triethylamine and pyridine; the second acid scavenger includes at least one of triethylamine and pyridine. Based on the above embodiments, the molecular structures of triethylamine and pyridine give them good solubility in tetrahydrofuran solvent, enabling them to form a homogeneous phase with the reaction system and ensuring the efficiency and timeliness of the proton capture process. Their molecular size is moderate, allowing them to effectively approach the reaction site without causing significant steric hindrance to the formation of the triazine ring.

[0027] In some embodiments, the mass ratio of the triazine cyclosilane coupling agent to the epoxy silane coupling agent is 1:(0.6-1). Based on the above embodiments, by limiting the ratio of rigid coupling agent to flexible coupling agent within the above range, the matching degree between rigid nodes and flexible segments in the cured network can be further optimized, resulting in better retention of the material's high-temperature mechanical properties.

[0028] In some embodiments, the viscosity of the terminal hydroxyl fluorosilicone raw rubber at 25°C is 1–200 Pa·s. Based on the above embodiments, this viscosity range ensures that the composition has good processability. At the same time, the polymer molecular chains at this viscosity have sufficient length and mobility, which, during curing, can provide initial toughness to the material through physical entanglement between molecular chains, and also ensure sufficient contact and reaction between the terminal silanol groups and the crosslinking agent and silane coupling agent. This lays the structural foundation for constructing a crosslinked network that simultaneously includes a Si-O-Si backbone formed by the main crosslinking agent and rigid triazine links and flexible ether segments introduced by the silane coupling agent.

[0029] In some embodiments, the reinforcing filler includes fumed silica with an average particle size of 10–50 nm. Based on the above embodiments, fumed silica can form Si-O-Si chemical bonds with triazine cyclosilane coupling agents, epoxy silane coupling agents, etc., through surface silanol groups, and participate in the establishment of a three-dimensional reinforcing network, thereby further improving the thermomechanical strength of the material.

[0030] In some embodiments, the crosslinking agent includes tetraethyl orthosilicate. Based on the above embodiments, tetraethyl orthosilicate, under the action of an organotin catalyst, can undergo a condensation reaction with the silanol groups at the ends of the fluorosilicone resin to form a stable Si-O-Si crosslinking network. This condensation reaction is mild, and its reaction pathway exhibits good chemical compatibility with the rigid triazine ring nodes and the flexible ether segments generated by epoxy ring opening in the system, without disrupting these key thermally stable structures. This characteristic ensures that while constructing a three-dimensional network framework, the synergistic crosslinking structure composed of rigid triazine ring nodes and flexible ether segments can be fully preserved. This allows the material to maintain framework stability at high temperatures while possessing excellent stress dissipation capabilities, ultimately resulting in good high-temperature resistance and mechanical properties.

[0031] Secondly, this application provides a method for preparing high-temperature resistant silicone resin, comprising: Provide raw materials for the silicone resin according to any embodiment of the first aspect; The raw materials are mixed and cured to obtain a high-temperature resistant silicone resin.

[0032] According to this application, since the raw materials of the silicone resin described in any embodiment of the first aspect are used, during the curing process, the triazine cyclosilane coupling agent and the epoxy group-containing silane coupling agent can construct a "rigid-flexible" crosslinking network in the fluorosilicone resin matrix. This method improves the thermal stability and mechanical adaptability of the crosslinking network through the synergistic effect of the rigid framework of the triazine ring and the flexible ether bonds formed by the ring-opening of the epoxy, thereby giving the fluorosilicone resin good heat resistance, high mechanical property retention, and long-term thermal aging stability.

[0033] In some embodiments, the method includes: Hydroxyl-terminated fluorosilicone raw rubber, reinforcing filler, triazine cyclosilane coupling agent, epoxy silane coupling agent and dibutyltin dilaurate are mixed at 60-100℃ for 10-30 minutes, and the air bubbles and moisture are removed under a vacuum of ≥-0.095MPa to obtain a uniformly mixed masterbatch. After the masterbatch cools to below 40°C, a crosslinking agent and an epoxy ring-opening catalyst are added and mixed at 20–60°C for 5–15 minutes. The resulting mixture is then molded or coated and pre-cured at 80–120°C for 0.5–2 hours, followed by post-curing at 150–200°C for 2–4 hours to obtain the high-temperature resistant silicone resin.

[0034] In some of the above embodiments, temperature and time control during the mixing stage allows for the full activation of triazine cyclosilane coupling agents and epoxy-containing silane coupling agents under the action of a catalyst. The silane end groups undergo preliminary hydrolysis and condensation reactions with the reinforcing filler surface and the fluorosilicone resin matrix, establishing preliminary interfacial chemical bonds. A vacuum environment effectively eliminates air bubbles and moisture from the system, preventing defects during high-temperature curing. Adding the crosslinking agent and epoxy ring-opening catalyst after cooling the masterbatch to below 40°C improves processing safety. In the subsequent stepped curing process, the pre-curing stage at 80–120°C allows the epoxy groups to fully open and crosslink under the action of a catalyst, constructing a flexible ether bond network. The subsequent post-curing stage at 150–200°C promotes the complete decomposition of the crosslinking agent, facilitating the condensation and crosslinking reaction of the fluorosilicone resin backbone, while simultaneously stabilizing the rigid triazine ring structure at high temperatures. Ultimately, a three-dimensional crosslinked network of rigid and flexible triazine ring-ether bond segments is formed, endowing the material with excellent high-temperature mechanical properties and thermal aging stability.

[0035] Compared with the prior art, the beneficial effects of this application are at least as follows: This application introduces a triazine-containing cyclosilane coupling agent and an epoxy-containing silane coupling agent synergistically into a fluorosilicone resin system, constructing a rigid-flexible triazine-epoxy bridging synergistic reinforcing network in situ during curing. This network structure improves the interfacial bonding strength between the filler and the resin matrix, enhances the thermochemical stability of the crosslinked network, and effectively reduces interfacial bond breakage and polymer backbone degradation under high-temperature oxidative conditions. Simultaneously, the rigid framework of the triazine ring and the flexible ether bond segments formed by epoxy ring opening synergistically inhibit high-temperature chain movement and disperse thermal stress, slowing down the material embrittlement process. This allows the resulting fluorosilicone resin to maintain good mechanical properties even after long-term high-temperature aging. This application achieves improved heat aging resistance and high-temperature mechanical property retention of fluorosilicone resin, and has broad engineering application prospects. Detailed Implementation

[0036] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.

[0037] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0038] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0039] In this specification, unless otherwise specified, "parts" refers to "parts by weight".

[0040] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0041] The hydroxyl-terminated fluorosilicone raw rubber has a viscosity of 120 Pa·s at 25°C, and the molar fraction of trifluoropropylmethylsiloxane repeating unit is approximately 60%. γ-(2,3-epoxypropoxy)propyltrimethoxysilane, CAS No.: 2530-83-8; γ-aminopropyltrimethoxysilane, CAS No.: 13822-56-5; Fumed silica, particle size 30nm; Preparation of triazine cyclosilane coupling agents: Under nitrogen protection, 0.1 mol of cyanuric chloride was added to tetrahydrofuran to prepare a 0.15 mol / L solution (total volume 0.67 L), which was then placed in an ice-water bath and cooled to 5 °C with stirring. A mixed solution consisting of 0.12 mol of γ-aminopropyltrimethoxysilane and 0.18 mol of triethylamine (making the molar ratio of γ-aminopropyltrimethoxysilane:cyanuric chloride:triethylamine 1.2:1:1.8) was slowly added dropwise. After the addition was complete, the reaction was continued to be stirred at 5 °C for 2 h to obtain a monosubstituted intermediate solution.

[0042] The reaction system was heated to 45°C, and a mixed solution consisting of 0.13 mol γ-aminopropyltrimethoxysilane and 0.20 mol triethylamine was added dropwise (making the molar ratio of γ-aminopropyltrimethoxysilane: cyanuric chloride: triethylamine in the second step 1.3:1:2.0). The reaction was stirred at 45°C for 5 h. After the reaction was completed, the mixture was cooled to 20°C, and the generated triethylamine hydrochloride was removed by filtration. The filtrate was concentrated under reduced pressure to recover tetrahydrofuran, yielding a pale yellow viscous liquid. This liquid was dissolved in an appropriate amount of hexane, frozen and allowed to stand at 5°C for 3 h to precipitate. The precipitate was filtered, and the solvent was removed by reduced pressure distillation to obtain a triazine ring-containing bissilane coupling agent.

[0043] Example 1 Preparation of high-temperature resistant silicone resin: Take 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 25 parts by weight of fumed silica, 1.5 parts by weight of triazine cyclosilane coupling agent, 1.2 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.3 parts by weight of dibutyltin dilaurate, add them to a mixer, and mix for 20 minutes at 80°C and a vacuum of -0.098 MPa to remove air bubbles and moisture, and obtain a uniformly mixed masterbatch.

[0044] After the masterbatch cools to 35°C, add 3 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of tetrabutylammonium bromide, and mix at 40°C for 10 minutes; then inject the resulting mixture into a mold, pre-cur at 100°C for 1 hour, and then post-cur at 180°C for 3 hours to obtain high-temperature resistant silicone resin.

[0045] Example 2 Preparation of high-temperature resistant silicone resin: Take 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 25 parts by weight of fumed silica, 1.5 parts by weight of triazine cyclosilane coupling agent, 1.2 parts by weight of 3-(2,3-epoxypropoxy)propyltriethoxysilane and 0.3 parts by weight of dibutyltin dilaurate, add them to a mixer, and mix for 20 minutes at 80°C and a vacuum of -0.098 MPa to remove air bubbles and moisture, and obtain a uniformly mixed masterbatch.

[0046] After the masterbatch cools to 35°C, add 3 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of tetrabutylammonium bromide, and mix at 40°C for 10 minutes; then inject the resulting mixture into a mold, pre-cur at 100°C for 1 hour, and then post-cur at 180°C for 3 hours to obtain high-temperature resistant silicone resin.

[0047] Comparative Example 1 Preparation of high-temperature resistant silicone resin: Take 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 25 parts by weight of fumed silica, 1.2 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.3 parts by weight of dibutyltin dilaurate, add them to a mixer, and mix for 20 minutes at 80°C and a vacuum of -0.098 MPa to remove air bubbles and moisture, and obtain a uniformly mixed masterbatch.

[0048] After the masterbatch cools to 35°C, add 3 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of tetrabutylammonium bromide, and mix at 40°C for 10 minutes; then inject the resulting mixture into a mold, pre-cur at 100°C for 1 hour, and then post-cur at 180°C for 3 hours to obtain high-temperature resistant silicone resin.

[0049] Comparative Example 2 Preparation of high-temperature resistant silicone resin: Take 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 25 parts by weight of fumed silica, 1.5 parts by weight of triazine cyclosilane coupling agent and 0.3 parts by weight of dibutyltin dilaurate, add them to a mixer, and mix for 20 minutes at 80°C and a vacuum of -0.098 MPa to remove air bubbles and moisture, and obtain a uniformly mixed masterbatch.

[0050] After the masterbatch cools to 35°C, add 3 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of tetrabutylammonium bromide, and mix at 40°C for 10 minutes; then inject the resulting mixture into a mold, pre-cur at 100°C for 1 hour, and then post-cur at 180°C for 3 hours to obtain high-temperature resistant silicone resin.

[0051] Comparative Example 3 Preparation of high-temperature resistant silicone resin: Take 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 25 parts by weight of fumed silica, 1.5 parts by weight of phenyltrimethoxysilane, 1.2 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.3 parts by weight of dibutyltin dilaurate, add them to a mixer, and mix for 20 minutes at 80°C and a vacuum of -0.098 MPa to remove air bubbles and moisture, and obtain a uniformly mixed masterbatch.

[0052] After the masterbatch cools to 35°C, add 3 parts by weight of tetraethyl orthosilicate and 0.03 parts by weight of tetrabutylammonium bromide, and mix at 40°C for 10 minutes; then inject the resulting mixture into a mold, pre-cur at 100°C for 1 hour, and then post-cur at 180°C for 3 hours to obtain high-temperature resistant silicone resin.

[0053] Test section The silicone rubber obtained from each embodiment and comparative example was made into type 1A dumbbell specimens according to GB / T528-2009. Then, according to GB / T528-2009, the tensile strength TS0 (MPa) and elongation at break ε0 (%) of the specimens were tested at a stretching rate of 50 mm / min. Samples of the same specifications were aged in hot air at 300℃ for 200h according to GB / T3512-2014, and then the tensile strength TS1 (MPa) and elongation at break ε1 (%) of the samples were tested according to GB / T528-2009 at a tensile rate of 50mm / min. The tensile strength retention rate δ (%) = TS1 / TS0 × 100% and the elongation at break retention rate η (%) = ε1 / ε0 × 100% were calculated.

[0054] The test results are shown in Table 1.

[0055] Table 1

[0056] According to Table 1, the retention rates of tensile strength and elongation at break in each embodiment are higher than those in the comparative sample, indicating that the high-temperature resistant silicone resin provided in this application can maintain more stable mechanical properties and structural integrity under high-temperature oxidative conditions, exhibiting excellent heat aging resistance. The possible reasons are as follows: In Comparative Example 1, only epoxy-containing silane coupling agents were used for flexible modification, without introducing triazine-containing silane coupling agents. The system lacked the rigid framework support of the triazine ring and the stabilizing effect brought by its high resonance energy. The electron-deficient characteristic of the triazine ring could have increased the breaking energy barrier of adjacent chemical bonds through inductive effects; its absence led to insufficient thermal stability of the crosslinked network. Under long-term thermo-oxidative aging, chain segment movement intensified, and the main chain was prone to degradation, resulting in lower retention rates of tensile strength and elongation at break after heat aging. In Comparative Example 2, no epoxy-containing silane coupling agent was used; the crosslinked network was constructed solely using triazine-containing silane coupling agents. This rigid network lacks flexible ether chains formed by the ring-opening of epoxy groups to absorb and disperse internal stress. This leads to the material being prone to microcracks and brittle fracture during thermal aging due to stress concentration, resulting in poor initial toughness and a decline in performance after aging. In Comparative Example 3, phenyltrimethoxysilane was used instead of the triazine-containing silane coupling agent. Although the benzene ring structure can also provide certain rigid sites and thermal stability, its resonance stability energy is lower than that of the triazine ring, and it lacks the induced stabilizing effect brought about by the strong electronegativity of the nitrogen atom in the triazine ring. As a result, its thermal stabilization effect as a rigid node is not as good as that of the triazine ring. Therefore, the retention rate of the obtained material after thermal aging is lower than that of the embodiments of this application.

[0057] The results of Examples 1 and 2 show that different types of epoxy-containing silane coupling agents have a certain impact on the heat resistance of the obtained silicone resins. When using γ-(2,3-epoxypropoxy)propyltrimethoxysilane, the prepared silicone resin exhibits higher tensile strength retention and elongation at break retention. This may be because the triazine-methoxy synergistic coupling system has a better effect on improving the crosslinking network density and interfacial thermal stability of the silicone resin. Furthermore, although the chemical structures are similar, replacing the methoxy group with an ethoxy group results in greater steric hindrance and lower hydrolytic reactivity of the ethoxy group, which somewhat delays the overall reaction efficiency of the dibutyltin dilaurate catalytic condensation and the tetrabutylammonium bromide catalytic epoxy ring-opening. This leads to a slightly less dense crosslinking network, thereby reducing the retention of strength and toughness.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A high-temperature resistant silicone resin, characterized in that, The raw materials include the following parts by weight: 100 parts by weight of hydroxyl-terminated fluorosilicone raw rubber, 0.5-2 parts by weight of triazine cyclosilane coupling agent, 0.05-1 parts by weight of dibutyltin dilaurate, 10-50 parts of reinforcing filler, and 0.5-5 parts by weight of crosslinking agent; The triazine cyclosilane coupling agent is obtained by a nucleophilic substitution reaction between some chlorine atoms in cyanuric chloride and an aminosilane coupling agent, and the molar ratio of cyanuric chloride to aminosilane coupling agent is 1:(2-3).

2. The silicone resin according to claim 1, characterized in that, The raw materials also include 0.5 to 2 parts by weight of an epoxy-containing silane coupling agent and 0.01 to 0.05 parts by weight of an epoxy ring-opening catalyst, wherein the epoxy-containing silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

3. The silicone resin according to claim 1, characterized in that, The triazine-containing cyclosilane coupling agent is prepared by the following steps: S1: Disperse cyanuric chloride, the first aminosilane coupling agent and the first acid scavenger in tetrahydrofuran, so that the amino group in the first aminosilane coupling agent undergoes a nucleophilic substitution reaction with some chlorine atoms in cyanuric chloride to obtain a partially substituted intermediate solution. S2: Add a second acid scavenger and a second aminosilane coupling agent to the partially substituted intermediate solution, so that the amino group in the second aminosilane coupling agent undergoes a nucleophilic substitution reaction with the remaining chlorine atoms in the partially substituted intermediate to obtain a triazine cyclosilane coupling agent.

4. The silicone resin according to claim 3, characterized in that, In step S1: The molar ratio of the cyanuric chloride, the first aminosilane coupling agent, and the first acid scavenger is 1:(1.0-1.5):(1.0-2).

5. The silicone resin according to claim 3, characterized in that, In step S2: The molar ratio of the second aminosilane coupling agent, the second acid scavenger, and cyanuric chloride in step S1 is (1.0-1.5):(1.0-2):

1.

6. The silicone resin according to claim 3, characterized in that, The triazine-containing cyclosilane coupling agent satisfies at least one of the following conditions: 1) The first aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane; 2) The second aminosilane coupling agent includes at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane; 3) The first acid scavenger includes at least one of triethylamine and pyridine; 4) The second acid scavenger includes at least one of triethylamine and pyridine.

7. The silicone resin according to claim 2, characterized in that, The mass ratio of the triazine-containing cyclosilane coupling agent to the epoxy-containing silane coupling agent is 1:(0.6-1).

8. The silicone resin according to any one of claims 1 to 7, characterized in that, The raw materials meet at least one of the following conditions: 1) The viscosity of the hydroxyl-terminated fluorosilicone raw rubber at 25°C is 1–200 Pa·s; 2) The reinforcing filler comprises fumed silica, wherein the average particle size of the silica is 10–50 nm; 3) The crosslinking agent includes tetraethyl orthosilicate; 4) The epoxy ring-opening catalyst includes at least one of tetrabutylammonium bromide and tetraethylammonium bromide.

9. A method for preparing high-temperature resistant silicone resin, characterized in that, include: Provide raw materials for the silicone resin according to claims 1 to 8; The raw materials are mixed and cured to obtain a high-temperature resistant silicone resin.

10. The method according to claim 9, characterized in that, include: Hydroxyl-terminated fluorosilicone raw rubber, reinforcing filler, triazine cyclosilane coupling agent, epoxy silane coupling agent and dibutyltin dilaurate are mixed at 60-100℃ for 10-30 minutes, and the air bubbles and moisture are removed under a vacuum of ≥-0.095MPa to obtain a uniformly mixed masterbatch. After the masterbatch cools to below 40°C, a crosslinking agent and an epoxy ring-opening catalyst are added and mixed at 20–60°C for 5–15 minutes. The resulting mixture is then molded or coated and pre-cured at 80–120°C for 0.5–2 hours, followed by post-curing at 150–200°C for 2–4 hours to obtain the high-temperature resistant silicone resin.